2019
DOI: 10.1002/14651858.cd010127.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative nutrition for the treatment of bladder cancer by radical cystectomy

Abstract: Background Radical cystectomy (RC) is the primary surgical treatment for muscle-invasive urothelial carcinoma of the bladder. This major operation is typically associated with an extended hospital stay, a prolonged recovery period and potentially major complications. Nutritional interventions are beneficial in some people with other types of cancer and may be of value in this setting too. Objectives To assess the e ects of perioperative nutrition in people undergoing radical cystectomy for the treatment of bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 55 publications
(51 reference statements)
0
22
0
Order By: Relevance
“…As previous epidemiologic studies have demonstrated, complications after cystectomy are associated with an increased risk of mortality. 33 - 35 In our series, mortality was significantly higher in group 1 versus 2 (34.5% v 5%, P = .0002).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…As previous epidemiologic studies have demonstrated, complications after cystectomy are associated with an increased risk of mortality. 33 - 35 In our series, mortality was significantly higher in group 1 versus 2 (34.5% v 5%, P = .0002).…”
Section: Discussionmentioning
confidence: 41%
“…Improving nutrition status with preoperative protein intake and nutritional therapy is related to a reduction in mortality. 33 Fast-track recovery protocols as the enhanced recovery after surgery have also been associated with lower length of hospital stay after RC. 31 In this study, we have observed similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, these complications are not common (overall catheter-related infection occurred in 0-10.7% of patients receiving preoperative PN, pneumothorax in 0-6.7% of patients, phlebitis in 0-1.8%, air embolus 0-1.6%, and thrombosis 0-0.5%) and they were relatively easy to detect and to treat. Appropriate catheter care is a measure to prevent infectious complications [36].…”
Section: Discussionmentioning
confidence: 99%
“…However, a Cochrane review exploring the evidence and quality of the studies found that the quality of evidence is low, and flagged the urgent need for high-quality research to better inform nutritional support interventions for people undergoing RC because of bladder cancer. 100 With regard to other important lifestyle factors such as smoking and risky drinking, which have a huge impact on physiological functions, there is generally strong evidence to support preoperative interventions to prevent postoperative complications if they are initiated 4-8 weeks before major surgery. There is still a lack of evidence to support short-term interventions, which is relevant to RC pathways, although studies have been performed, but are yet to be published.…”
Section: Dovepressmentioning
confidence: 99%